(untitled) (Research, Society and Development, 2021)
Semen cryopreservation is responsible for decrease the gamete fertility, due to structural and functional damages. Among the various causes, oxidative stress, resulting from the higher generation of reactive oxygen species (ROS), has been attributed to affect semen quality. Thus, it was objectified evaluate the effect of Trolox on ram and goat sperm, subjected to freezing. Semen pools of goat (n=5) and ram (n=6) were diluted in skimmed milk (7% glycerol) or Tris-egg yolk (5% glycerol) extender, respectively, added or not of Trolox (0, 20 or 40 μM/ml) and frozen. After thawing (37 °C/30 s), aliquots of semen were evaluated for lipid peroxidation by high performance liquid chromatography, coupled with a photodiode array detector (HPLC-DAD), and flow cytometry (C11-BODIPY581/591), besides of plasma membrane and acrosome integrity by fluorescence microscopy, and sperm kinetics by computerized sperm analysis (CASA). The antioxidant treatment with Trolox did not determine significant effects (p>0.05) on lipid peroxidation, plasma membrane integrity, acrosomal integrity and on the kinetic parameters evaluated. Thus, it is concluded that Trolox (20 or 40 μM) did not have a protective or deleterious effect on goats and ram sperm, submitted to freezing.